Information Technology Risk Management on Semarang Regency BPS Application Using ISO31000:2018 - Sandra Gita; Penidas Fiodinggo Tanaem (Universitas Bina Darma, 2022)
BPS Semarang Regency is an agency engaged in calculating census statistics, BPS Semarang Regency has implemented SI / IT to support the performance carried out. BPS Semarang Regency has an application in the form of ICS or better known as the Integrated Collection System, where this application is used in calculating population censuses, economic censuses, and agricultural censuses. However, there is always a risk from the application, one of the risk impacts that has occurred such as human error, the server that suddenly goes down becomes an obstacle for users in running the application. With SI/IT risk management conducted to minimize risk, it will be carried out using the ISO31000:2018 framework. It is hoped that this risk management can be used as a guideline for BPS Semarang Regency in dealing with existing risks. The results of this risk analysis are in the form of proposed recommendations from risk actions on risks based on the impact and frequency of events. That way BPS Semarang Regency can prevent and minimize risks so that the function of the ICS application can run optimally.